Evaporation‐ and Solution‐Process‐Feasible Highly Efficient Thianthrene‐9, 9′, 10, 10′‐Tetraoxide‐Based Thermally Activated Delayed Fluorescence Emitters with Reduced Efficiency Roll‐Off. Issue 1 (9th November 2015) - Xie, Gaozhan; Li, Xianglong; Chen, Dongjun; Wang, Zhiheng; Cai, Xinyi; Chen, Dongcheng; Li, Yunchuan; Liu, Kunkun; Cao, Yong; Su, Shi‐Jian
Abstract : Two novel evaporation‐ and solution‐process‐feasible thermally activated delayed fluorescence emitters, green‐light‐emission ACRDSO2 and yellow‐light‐emission PXZDSO2, based on a brand‐new electron‐acceptor moiety thianthrene‐9, 9′, 10, 10′‐tetraoxide, are developed for organic light‐emitting diodes. The solution‐processed devices, without any hole‐transport layer, exhibit competitive performance and reduced efficiency roll‐off compared with corresponding vacuum‐deposited devices.